1999
DOI: 10.1097/00005392-199905000-00036
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficacy and Safety of Tolterodine Compared to Placebo in Detrusor Overactivity

Abstract: Tolterodine administration resulted in a significant decrease in the frequency of voiding and improved voided volume but it was seldom associated with troublesome or severe side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
18
0
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 7 publications
6
18
0
2
Order By: Relevance
“…Overall, the efficacy of tolterodine in patients with MI was similar to that in a parallel cohort of patients with UI alone, and was in line with earlier studies with tolterodine in patients with OAB [6,8,9,11,13]. From these findings, initial treatment with tolterodine therefore appears warranted for patients reporting mixed symptoms of stress and UI, provided other local or metabolic pathological causes of such symptoms have been excluded.…”
Section: Discussionsupporting
confidence: 84%
“…Overall, the efficacy of tolterodine in patients with MI was similar to that in a parallel cohort of patients with UI alone, and was in line with earlier studies with tolterodine in patients with OAB [6,8,9,11,13]. From these findings, initial treatment with tolterodine therefore appears warranted for patients reporting mixed symptoms of stress and UI, provided other local or metabolic pathological causes of such symptoms have been excluded.…”
Section: Discussionsupporting
confidence: 84%
“…These observations were in accordance with earlier findings established for predominantly Caucasian populations. [11][12][13]16 Tolterodine was well tolerated in the present study, and was significantly better tolerated than oxybutynin. The overall incidence of adverse events was significantly lower in patients receiving tolterodine than in those treated with oxybutynin, which may explain the lower rate of withdrawal due to adverse events among tolterodine recipients (10% vs 16% on oxybutynin).…”
Section: Discussionsupporting
confidence: 49%
“…16 Tolterodine, a relatively new antimuscarinic agent, was developed specifically for the treatment of OAB. [17][18][19][20][21][22][23][24][25] A study of 714 patients with OAB revealed that immediate-release tolterodine 2 mg twice/day was effective, but 41% of the patients reported dry mouth. 20 Similar to oxybutynin, extended-release tolterodine improved efficacy of reducing urge incontinence episodes and lowered the frequency of dry mouth compared with the immediate-release formulation.…”
mentioning
confidence: 99%